Essential Roles of Two FRQ Proteins (Frq1 and Frq2) in Beauveria bassiana’s Virulence, Infection Cycle, and Calcofluor-Specific Signaling - Tong, Sen-Miao; Gao, Ben-Jie; Peng, Han; Feng, Ming-Guang (Applied and environmental microbiology, 2021)
Opposite nuclear rhythms of two distinct FRQ proteins (Frq1 and Frq2) coexisting in an asexual fungal insect pathogen have been shown to orchestrate the fungal nonrhythmic conidiation in vitro in a circadian day independent of photoperiod change. This paper reports essential roles of both Frq1 and Frq2, but a greater role for Frq2, in sustaining the fungal virulence and infection cycle since either frq1 or frq2 deletion led to marked delay of lethal action against a model insect and drastic reduction of conidial yield on insect cadavers. Two FRQ proteins (Frq1 and Frq2) distinct in molecular mass and structure coexist in Beauveria bassiana , an asexual insect-pathogenic fungus. Frq1 and Frq2 have been proven to have opposite nuclear rhythms that can persistently activate developmental activator genes and hence orchestrate nonrhythmic conidiation in vitro under light or in darkness. Here, we report the essentiality of either FRQ, but Frq2 being more important than Frq1, for the fungal virulence and infection cycle. The fungal virulence was attenuated significantly more in the absence of frq2 than in the absence of frq1 through either normal cuticle infection or cuticle-bypassing infection by intrahemocoel injection, accompanied by differentially reduced secretion of Pr1 proteases required for the cuticle infection and delayed development of hyphal bodies in vivo , which usually propagate by yeast-like budding in the host hemocoel to accelerate insect death from mycosis. Despite insignificant changes in radial growth under normal, oxidative, and hyperosmotic culture conditions, conidial yields of the Δ frq1 and Δ frq2 mutants on insect cadavers were sharply reduced, and the reduction increased with shortening daylight length on day 9 or 12 after death, indicating that both Frq1 and Frq2 are required for the fungal infection cycle in host habitats. Intriguingly, the Δ frq1 and Δ frq2 mutants showed hypersensitivity and high resistance to cell wall-perturbing calcofluor white, coinciding respectively with the calcofluor-triggered cells′ hypo- and hyperphosphorylated signals of Slt2, a mitogen-activated protein kinase (MAPK) required for mediation of cell wall integrity. This finding offers a novel insight into opposite roles of Frq1 and Frq2 in calcofluor-specific signal transduction via the fungal Slt2 cascade. IMPORTANCE Opposite nuclear rhythms of two distinct FRQ proteins (Frq1 and Frq2) coexisting in an asexual fungal insect pathogen have been shown to orchestrate the fungal nonrhythmic conidiation in vitro in a circadian day independent of photoperiod change. This paper reports essential roles of both Frq1 and Frq2, but a greater role for Frq2, in sustaining the fungal virulence and infection cycle since either frq1 or frq2 deletion led to marked delay of lethal action against a model insect and drastic reduction of conidial yield on insect cadavers. Moreover, the frq1 and frq2 mutants display hypersensitivity and high resistance to cell wall perturbation and have hypo- and hyperphosphorylated MAPK/Slt2 in calcofluor white-triggered cells, respectively. These findings uncover a requirement of Frq1 and Frq2 for the fungal infection cycle in host habitats and provide a novel insight into their opposite roles in calcofluor-specific signal transduction through the MAPK/Slt2 cascade.